Digital play in young children's numeracy learning. Issue 2 (June 2019) - Disney, Leigh; Barnes, Alan; Ey, Lesley; Geng, Gretchen
Advances in technology have seen a proliferation of touch-screen interfaces available to young children. These screens have changed the way in which young children engage with digital technology; with increased exposure and use, it raises debates about the suitability of integrating digital technology within early childhood settings. There are limited empirical studies that investigate the appropriateness of emergent digital technology within the field of early childhood. Based upon the TPACK model, this timely paper thus discussed the Digital Play Model (Numeracy) and reported on a project investigating the integration of digital technologies into childcare settings. In particular, the focus of this paper was to report on the use of games using a gestural interface device have on 3- to 4-year-old children's ability to learn numeracy concepts. This study found that young children's numeracy learning outcomes were improved. This paper also provided empirical evidence of the use of Apps via iPad technologies on young children's numeracy learning, with an implication to a need for a pedagogical model for successful integration of digital technology within early childhood settings.